DOI: 10.31274/rtd-180813-8788
|View full text |Cite
|
Sign up to set email alerts
|

The use of electronic feeders in genetic improvement programs for swine

Abstract: Introduction Materials and Methods Results Discussion Implications Literature Cited CHAPTER 3. A MODEL TO ADJUST DAILY FEED INTAKE RECORDS FOR ERRORS IN DATA FROM ELECTRONIC SWINE FEEDERS Abstract Introduction Materials and Methods Results and Discussion Implications Literature Cited CHAPTER 4. A COMPARISON OF METHODS OF EDITING DATA FROM ELECTRONIC SWINE FEEDERS Abstract Introduction Materials and Methods Results and Discussion 80 Implications 90 Literature Cited CHAPTER 5. PERFORMANCE OF GROWING AND FINISHIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…A curvilinear pattern of ADG (Figure 1) was detected for pigs sired by boars from both time periods. Similar daily BW accretion rates were reported by Casey (2003) and Moeller et al (1998). As previously mentioned, results of this study for daily BW accretion are contrary to what would be expected from the genetic and phenotypic trends reported by Chen et al (2002) and Kaplon et al (1991) and may be explained by the unequal distribution of records among sexes in this study (Table 1).…”
Section: Serially Measured Traitssupporting
confidence: 53%
“…A curvilinear pattern of ADG (Figure 1) was detected for pigs sired by boars from both time periods. Similar daily BW accretion rates were reported by Casey (2003) and Moeller et al (1998). As previously mentioned, results of this study for daily BW accretion are contrary to what would be expected from the genetic and phenotypic trends reported by Chen et al (2002) and Kaplon et al (1991) and may be explained by the unequal distribution of records among sexes in this study (Table 1).…”
Section: Serially Measured Traitssupporting
confidence: 53%
“…Several indexes have been defined that combine the effect of temperature and relative humidity, adjusted for pigs of different live weights (Lucas et al, 2000). More studies are needed that measure individual temperature continuously and simultaneously in large groups, in combination with environmental and production data, such as the number of visits to feeding stations (Casey, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In practice, longitudinal measurements of FI and BW data are often missing for substantial parts of growth period, including at the beginning and end. Major missing data occur when pigs are switched between electronic and commercial feeders to enlarge the test capacity because of the high expense of electronic feeders (Casey 2003;Eissen et al 1999;Schulze et al 2001;, and are caused by data errors and malfunction of electronic feeders (Casey et al 2005;Eissen et al 1998). Several studies have shown that missing FI information on different parts of the growth period has a limited effect on the accuracy of evaluating ADFI (Casey 2003;Eissen et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Major missing data occur when pigs are switched between electronic and commercial feeders to enlarge the test capacity because of the high expense of electronic feeders (Casey 2003;Eissen et al 1999;Schulze et al 2001;, and are caused by data errors and malfunction of electronic feeders (Casey et al 2005;Eissen et al 1998). Several studies have shown that missing FI information on different parts of the growth period has a limited effect on the accuracy of evaluating ADFI (Casey 2003;Eissen et al 1999). However, there have been few studies on the effect of missing data on evaluation of feed intake and body weight curves, which requires sophisticated statistical models to inter-and extrapolate FI and BW curves for individual pigs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation